Dielectric imaging for electrophysiology procedures: The technology, current state, and future potential. (4th March 2021) - Abeln, Bob G.S.; van den Broek, Johannes L.P.M.; van Dijk, Vincent F.; Balt, Jippe C.; Wijffels, Maurits C.E.F.; Dekker, Lukas R.C.; Boersma, Lucas V.A.
Abstract: Electroanatomic mapping systems have become an essential tool to guide the identification and ablation of arrhythmic substrate. Recently, a novel guiding system for electrophysiology procedures was introduced that uses dielectric sensing to perform high resolution anatomical imaging. Dielectric imaging systems use electrical fields to differentiate anatomic structures based on their conductivity and permittivity. This technique enables non‐fluoroscopic, noncontact mapping of anatomic structures, assessment of pulmonary vein occlusion state during cryoballoon ablation, and has the potential to assess for additional tissue characterization including tissue thickness and tissue type. This article elaborates on the functioning and potential of dielectric imaging systems and provides two cases to illustrate the clinical impact for electrophysiology procedures.